A novel mutation, Ile344Asn, in microsomal triglyceride transfer protein abolishes binding to protein disulfide isomerase - Swati Valmiki; Cindy Bredefeld; M. Mahmood Hussain (Journal of Lipid Research)
Microsomal triglyceride transfer protein (MTP) plays crucial roles in the assembly and secretion of apolipoprotein B-containing lipoproteins and loss of function MTP variants are associated with abetalipoproteinemia, a disease characterized by the absence of these lipoproteins. MTP is a heterodimeric protein of two subunits, MTP and protein disulfide isomerase (PDI). In this study, we report a proband with abetalipoproteinemia who was monitored annually for 10 years in her third decade and had very low plasma lipids and undetectable apoB-containing lipoproteins. Genetic testing revealed biallelic variants in the MTTP gene. She has a well-documented nonsense mutation Gly865∗ that does not interact with the PDI subunit. She also has a novel missense MTP mutation, Ile344Asn. We show that this mutation abrogates lipid transfer activity in MTP and does not support apolipoprotein B secretion. This residue is present in the central α-helical domain of MTP and the substitution of Ile with Asn at this position disrupts interactions between MTP and PDI subunits. Ile344 is away from the known MTP:PDI interacting sites identified in the crystal structure of MTP suggesting that MTP:PDI interactions are more dynamic than previously envisioned. Identification of more missense mutations will enhance our understanding of the structure-function of MTP and the role of critical residues in these interactions between the two subunits. This knowledge may guide us in developing novel treatment modalities to reduce plasma lipids and atherosclerosis.